Extending kinome coverage by analysis of kinase inhibitor broad profiling data. Issue 6 (June 2015) - Jacoby, Edgar; Tresadern, Gary; Bembenek, Scott; Wroblowski, Berthold; Buyck, Christophe; Neefs, Jean-Marc; Rassokhin, Dmitrii; Poncelet, Alain; Hunt, Jeremy; van Vlijmen, Herman
Graphical abstract Analysis of the scientific literature based on the Eidogen-Sertanty Kinase Knowledgebase shows that there are 164 and 235 human kinases (from a total of 518) for which more than 10 ligands per kinase are known with potencies better than 10 or 100 nm, respectively. This explored kinome was extended with kinase broad profiling data using the DiscoveRx and Millipore kinase assay panels. The detailed analysis of the profiling of 3368 selected kinase inhibitors on 456 kinases in the DiscoveRx KINOMEscan format delivers a number of insights. Selective compounds identified through broad kinase inhibitor profiling can be used in target validation, enable jumpstarting new kinase drug discovery projects, and chart new biological space via phenotypic screening.